ANALISA KERUSAKAN BANTALAN BOLA (BALL BEARING) JENIS DEEP GROOVE PADA LORI PABRIK KELAPA SAWIT DAN CARA PENANGGULANGANNYA - Arif Rahman Saleh (Jurnal APTEK, 2014)
Bunches of fresh fruit brought to the boiling station ( sterilizer ) by using lorries . Work environment changing and dynamic loading causes a decrease in the performance of a lorry wheel bearing causing damage to the average Lori damage after operating for 250 hours ( 31 days of production ) with the same form of damage . To find the cause of the damage done testing includes a visual examination , Fraktografi , hardness , metallographic and chemical composition . Makrofraktografi of testing showed damage the ball bearing on the runway outside the outer runway preceded by experienced chipped with fatigue fracture surface shape with a length of 26 mm , followed by static fracture ( sudden ) due to compressive load